Anaplastic and meningothelial meningiomas in a single tumor: A "dedifferentiated meningioma"?. Issue 6 (3rd July 2016) - Shintaku, Masayuki; Adachi, Yasushi; Arai, Atsushi; Koyama, Junji
Abstract : The patient was a 74‐year‐old man, who developed progressive cognitive impairment and gait instability. Neuroradiological examination demonstrated a large and predominantly extra‐axial tumor spreading over the bilateral frontal base, indicative of olfactory groove meningioma. The greater part of the resected tumor consisted of a dense, patternless proliferation of large, round or polygonal cells, and compactly fascicular growth of spindle cells. Tumor cells showed markedly anaplastic cytological features. In small areas of the tumor, a typical meningothelial meningioma showing no cellular atypism was found. Both tumor components were closely juxtaposed and no pathological features of an intermediate grade (atypical meningioma) were noted. Shortly after the operation, the patient developed a local recurrence of the tumor and multiple metastases to the cerebrum, bone and skin. Anaplastic meningioma is a rare, highly malignant neoplasm which arises de novo or as a result of the progressive transformation of a low‐grade meningioma. The coexistence of anaplastic and low‐grade components in a single meningeal tumor has been rarely reported. This dimorphic appearance is reminiscent of "dedifferentiation", a phenomenon infrequently seen in various mesenchymal and salivary gland neoplasms. We think that the term "dedifferentiated meningioma" can be appropriately applied to tumors such as that reported herein.